2004
DOI: 10.1016/j.preteyeres.2004.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Genetic factors of age-related macular degeneration

Abstract: Age-related macular degeneration (AMD) is a leading cause of blindness in the United States and developed countries. Although the etiology and pathogenesis of AMD remain unknown, a complex interaction of genetic and environmental factors is thought to exist. The incidence and progression of all of the features of AMD are known to increase significantly with age. The tendency for familial aggregation and the findings of gene variation association studies implicate a significant genetic component in the developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
46
0
3

Year Published

2005
2005
2011
2011

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 85 publications
(50 citation statements)
references
References 157 publications
(199 reference statements)
1
46
0
3
Order By: Relevance
“…To date, age, cigarette smoking, nutrition, and exposure to light have been identified as AMD risk factors [Age-Related Eye Disease Study Research Group, 2000Seddon et al, 2001;Husain et al, 2002;Hyman and Neborsky, 2002]. Various studies also indicate a significant genetic contribution to AMD risk [Tuo et al, 2004a]. For example, it has been reported that advanced AMD is more prevalent in Caucasian populations when compared with other races that possess higher levels of uveal pigmentation and skin melanin [Friedman et al, 1999;Age-Related Eye Disease Study Research Group, 2000].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, age, cigarette smoking, nutrition, and exposure to light have been identified as AMD risk factors [Age-Related Eye Disease Study Research Group, 2000Seddon et al, 2001;Husain et al, 2002;Hyman and Neborsky, 2002]. Various studies also indicate a significant genetic contribution to AMD risk [Tuo et al, 2004a]. For example, it has been reported that advanced AMD is more prevalent in Caucasian populations when compared with other races that possess higher levels of uveal pigmentation and skin melanin [Friedman et al, 1999;Age-Related Eye Disease Study Research Group, 2000].…”
Section: Introductionmentioning
confidence: 99%
“…The higher occurrence of AMD among monozygotic twins and first-degree relatives of AMD patients when compared with spouses and unrelated individuals also indicates a significant genetic component in AMD risk [Meyers et al, 1995;Seddon et al, 2005]. A few studies have been able to demonstrate an association between AMD and various single nucleotide polymorphisms (SNPs) [Tuo et al, 2004a;Edwards et al, 2005;Haines et al, 2005;Klein et al, 2005;Tuo et al, 2006]. Apolipoprotein E (ApoE) is a multiple function protein highly expressed in the liver, brain, and retina [Anderson et al, 2001;Ribalta et al, 2003].…”
Section: Introductionmentioning
confidence: 99%
“…AMD is characterized by a progressive loss of central vision attributable to degenerative and neovascular changes that occur at the interface between the neural retina and the underlying choroid. At this location are the retinal photoreceptors, the retinal pigmented epithelium (RPE), a basement membrane complex known as Bruch's membrane (BM) and a network of choroidal capillaries.The prevailing view is that AMD is a complex disorder stemming from the interaction of multiple genetic and environmental risk factors (3,4). Familial aggregation studies indicate that a genetic contribution can be identified in up to 25% of the cases (5).…”
mentioning
confidence: 99%
“…The prevailing view is that AMD is a complex disorder stemming from the interaction of multiple genetic and environmental risk factors (3,4). Familial aggregation studies indicate that a genetic contribution can be identified in up to 25% of the cases (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation